Psicanalistas e a escuta do racismo à brasileira: escrevivências, po-éticas e política - Alves, Brígida Cavalcanti (2024)
This dissertation is the result of my concerns as a woman, a black woman and a psychoanalyst, especially when listening to the denunciations made by self-declared black patients of the positions of coloniality present in the work of Brazilian psychoanalysts. It is well known that in the 19th century racist and scientific discourses engendered policies of whitening and miscegenation of our people, which produced and produces consequences in the modes of subjectivation present in this territory. Therefore, an ethical and welcoming approach to racial issues is not given or guaranteed, and it is necessary for other analyzers to appear in order to think about the formation and work of psychoanalysis and psychoanalysts in Brazil. So, faced with this scenario, a first question emerged: What is the place of the psychoanalyst in listening to racism against black people in Brazil? To do this, we looked to the theoretical guidelines given by Sigmund Freud and Jacques Lacan on the training of psychoanalysts and listening to the unconscious, but due to the processes of colonization and Brazilian cultural neurosis, other positions had to be adopted. Decolonial and black theories appeared here as new lenses in order to investigate racial and racist policies, the white narcissistic pact that sustains this logic of violence and segregation directed at the black population, and to foster knowledge and ancestral technologies of black resistance to such confrontations. Based on the weaving of writing experiences, with experiences that permeate my body and professional training, and interviews with practicing psychoanalysts in Rio Grande do Norte, this research can provide elaborations on the place of psychoanalytic listening in the articulation and disarticulation of racism, the denials and practices of coloniality in the analytical setting and the possible inventions of this clinical device when in composition with politics.